Defusing SARS-CoV-2: Emergency Brakes in a Vaccine Failure Scenario - Fernandez, Ariel (2020)
Deactivation of primed SARS-CoV-2 prior to cell entry constitutes an emergency brake in COVID-19 infection if vaccine-induced antibodies fail to block recognition of the human angiotensin-converting enzyme 2 (hACE2) receptor. The timing and locus for the therapeutic intervention are dictated by the cell entry mechanism and by the selective advantage of the dominant D614G mutation.